STUDY THE EFFECT OF ADENOSINE DEAMINASE ENZYME IN INDUCES CYTOGENETIC AND HISTOPATHOLOGICAL CHANGES IN RATS SKIN AND EYES TREATED WITH SUMICIDIN - Al-Qaisi, Bushra Ibrahim (The Iraqi Journal of Veterinary Medicine, 2000)
The present investigation aimed to study the Adenosine Deaminase activity in induction Cytogentic and histopathological change in skin and eyes of sumicidine treated rats. The study Included. 1-Adenosine deaminase activity . 2-Total serum protein. 3-Micronuclei in binucleated cell. 4-Histopathological changes in skin and eyes. 19 white male rats were used . They are randomly allocated into 3 groups : 1st group was fed 2% sumicidine for 15 days. 2nd group was fed 2% heating sumicidine for 15 days . 3rd group was kept on normal diet. Blood Adenosine Deaminase activity and Total serum protein in 1 and 2 group significantly decreased at 15 and 30 days of treated. The results indicated that sumicidine increased significantly micronucleus in group 1 and 2. Multifocal granulomatous lesions in skin & eyes of group 1 and 2 were found characterized by highly aggregation of cells (Lymphocytes, Macrophages, Foreign body giant cells and fibroblasts). In conclusion , Sumicidine even heated accompaying in decreased in decreased Adenosine Deaminase activity and total serum protein , in part a possible factor in the cytogenetic effect and accompanying granuloma formation in skin and eye .